2020
DOI: 10.3390/ijms21082958
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin and Testicular Function—Is It Necessary?

Abstract: The role of kisspeptin in stimulating hypothalamic GnRH is undisputed. However, the role of kisspeptin signaling in testicular function is less clear. The testes are essential for male reproduction through their functions of spermatogenesis and steroidogenesis. Our review focused on the current literature investigating the distribution, regulation and effects of kisspeptin and its receptor (KISS1/KISS1R) within the testes of species studied to date. There is substantial evidence of localised KISS1/KISS1R expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 73 publications
(149 reference statements)
3
25
0
Order By: Relevance
“…The Kisspeptin system is an evolutionarily conserved signaling system notably involved in the central control of reproduction, but also expressed at periphery within gonads, gametes, and reproductive tracts in both sexes [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. In the present study, we preliminarily analyzed the presence of Kiss1 and Kiss1R in the dog testis and then we evaluated the system in parallel to the functional maturation of sperm attributes and storage along the transit in the epididymis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Kisspeptin system is an evolutionarily conserved signaling system notably involved in the central control of reproduction, but also expressed at periphery within gonads, gametes, and reproductive tracts in both sexes [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. In the present study, we preliminarily analyzed the presence of Kiss1 and Kiss1R in the dog testis and then we evaluated the system in parallel to the functional maturation of sperm attributes and storage along the transit in the epididymis.…”
Section: Discussionmentioning
confidence: 99%
“…Today, it is well-established that the Kisspeptin system plays a pivotal key role in several aspects of reproduction not only by the direct regulation of GnRH but also by driving the onset of puberty, sex steroid feedback mechanisms [ 5 , 10 , 11 ], and regulating seasonal reproduction in domestic animals [ 12 , 13 , 14 , 15 ], Syrian hamster [ 16 ], amphibians [ 17 , 18 ], and some fish [ 19 ]. Alongside the central modulatory role, the Kisspeptin system was found to regulate gonadal functions at peripheral in both females [ 20 , 21 , 22 ] and males [ 23 , 24 , 25 , 26 ]. In the testis, the presence of Kiss1 and Kiss1R was detected in Sertoli cells and interstitial cells, while not fully concordant data were found on the presence of Kisspeptin system in germline cells [ 24 , 25 ] (for recent review).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…KISS1 is also distributed in seminal plasma [24]. Kisspeptin effect on sperm function is translated by increasing intracellular Ca2+ in spermatozoa in addition to increasing sperm motility with a transient hyperactivation of sperm [24]. A recent study by Zou et al conducted among 666 Chinese student volunteers showed a positive association between total seminal plasma kisspeptin and semen quality, which was determined by the concentration of the sperm, total sperm count, and motile sperm count (P<0.01) [25] Pathological effect of kisspeptin on HPG Kisspeptin regulates various pathways, including follicular development, oocyte formation, ovulation, ovarian steroidogenesis, embryo implantation, and placenta in females.…”
Section: Control Of Kisspeptin In Reproductionmentioning
confidence: 99%
“…Research shows that there is a direct effect of kisspeptin on the male gamete. This is established by the presence of the KISS1 receptor in the spermatozoa, mainly in the head (post-acrosomal region), neck, and flagellum in humans [ 24 ]. KISS1 is also distributed in seminal plasma [ 24 ].…”
Section: Reviewmentioning
confidence: 99%